43. SEPSIS PATHOGENS AND ANTIBIOTIC RESISTANCE IN THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: The aim of this study was to determine the micro-organisms causing sepsis and their antimicrobial resistance in sepsis patients admitted to Thong Nhat Hospital from April 30th, 2023, to May 01st, 2024.Subject and Method: Cross-sectional, descriptive research on the patient had a positive blood culture result at Thong Nhat Hospital.Result: Among 705 cases of blood culture-positive patients, bacteria accounted for 97.87%, while fungi accounted for 2.13%. The most prevalent microorganisms were Coagulasenegative Staphylococci (28.70%), E. coli (25.22%), S. aureus (10.72%), and K. pneumoniae (6.67%). The rates of ESBL production in E. coli and K. pneumoniae were 43.1% and 10.9%, respectively. E. coli showed high sensitivity to amikacin, gentamicin, carbapenem, and piperacillintazobactam, tobramycin. However, E. coli exhibited resistance to over 50% of aztreonam (88.2%), ampicillin (86.6%), ceftriaxone (63.1%), and fluoroquinolones like ciprofloxacin (66.5%) and levofloxacin (59.2%). For K. pneumoniae, antibiotics to which it remained highly sensitive included the carbapenem group, such as ertapenem (75.4%), imipenem (75.4%), and piperacillin-tazobactam (87.8%). K. pneumoniae exhibited resistance to ampicillin (100.0%), aztreonam (87.5%), levofloxacin (40.0%), ceftriaxone (39.1%), and ciprofloxacin (39.1%). P. aeruginosa showed resistance to most antibiotics, with carbapenem resistance rates of 45.5% for imipenem and 33.3% for meropenem. Regarding S. aureus, the highest antibiotic resistance rates were observed for benzypenicillin (89.2%), clindamycin (66.2%) and erythromycin (66.2%). Over 90% of S. aureus strains were sensitive to vancomycin, linezolid, teicoplanin, and tigecycline. In addition, Candida spp. exhibited high sensitivity to antifungal drugs.Conclusion: In 705 blood culture-positive patients, bacteria accounted for 97.87%, while fungi accounted for 2.13% of the cases. The most common fungi identified were Candida spp., with over 80% susceptibility to antifungal agents. Among the prevalent bacterial strains isolated from blood cultures, Coagulase-negative Staphylococci (28.70%), E. coli (25.22%), S. aureus (10.72%), and K. pneumoniae (6.67%) were the most frequent. The rates of ESBL production among E. coli and K. pneumoniae were 43.1% and 10.9%, respectively. The strains with high multidrug resistance were E. coli, followed by S. aureus, with MRSA accounting for 62.2%. Data regarding the antibiotic resistance patterns observed in blood culture isolates play a pivotal role in the clinical decision-making process, facilitating healthcare providers in the selection of appropriate antibiotic treatments.
Keywords: sepsis; antibiotic resistance; Thong Nhat Hospital